Boron‐Dependency of Molybdenum Boride Electrocatalysts for the Hydrogen Evolution Reaction. (10th April 2017) - Park, Hyounmyung; Encinas, Andrew; Scheifers, Jan P.; Zhang, Yuemei; Fokwa, Boniface P. T.
Abstract: Molybdenum‐based materials have been considered as alternative catalysts to noble metals, such as platinum, for the hydrogen evolution reaction (HER). We have synthesized four binary bulk molybdenum borides Mo2 B, α‐MoB, β‐MoB, and MoB2 by arc‐melting. All four phases were tested for their electrocatalytic activity (linear sweep voltammetry) and stability (cyclic voltammetry) with respect to the HER in acidic conditions. Three of these phases were studied for their HER activity and by X‐ray photoelectron spectroscopy (XPS) for the first time; MoB2 and β‐MoB show excellent activity in the same range as the recently reported α‐MoB and β‐Mo2 C phases, while the molybdenum richest phase Mo2 B show significantly lower HER activity, indicating a strong boron‐dependency of these borides for the HER. In addition, MoB2 and β‐MoB show long‐term cycle stability in acidic solution.